NEW DATA ON THE MORPHOLOGY OF SHELL MUSCLES IN CAMBRIAN HELCIONELLOID MOLLUSKS - Parkhaev P.Yu. (My University, 2004)
Scars of shell muscles have been discovered on internal molds of helcionelloid mollusks of the family Stenothecidae for the first time. The localization of the scars is similar to that in the family Coreospiridae. Since these two families evolved from the ancestral group independently, similar shell muscle systems of Cambrian helcionelloid mollusks may be explained by parallel development.
Keywords: morphology; Cambrian; univalved mollusks; shell muscles; Paleozoic::Cambrian; Палеозой::Кембрийская